O teorema de Cauchy na mecânica dos fluidos - Menezes, Paulo César Almeida (2010)
The present work shows Cauchy's Theorem on its classical form, and it has the objective of weakening their statements, and provides aplications in continuum mechanics. The metodology used here is the axiomatic, that is, a presentation of basic concepts with fundamental results and theirs proofs. The main result here is Theorem 5, since it shows that for a Cauchy ux weakly balanced with density f there is a field such that f is linear in almost every points of R. The conclusion obtained is we can substitute the statement that f is a continuum function of position and have similar conclusions.